2009
DOI: 10.12693/aphyspola.115.123
|View full text |Cite
|
Sign up to set email alerts
|

Heat Capacity of Heavy Fermion Compound CeCu4Ga in High Magnetic Fields

Abstract: The heat capacity in the applied magnetic field up to 9 T, susceptibility and magnetization of polycrystalline CeCu4Ga are presented. Magnetic ordering was not observed down to 2 K. For temperature T < 200 K a Curie-Weiss behavior is observable giving an effective magnetic moment µ eff = 2.53 µB/f.u. The experimental value of µ eff is close to the calculated one for a free Ce 3+ ion (µ eff = 2.54 µB/f.u.), thus indicating the presence of well localized magnetic moments carried by the stable Ce 3+ ions. At low … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…CeCu 4 Ga has been already widely studied and it was verified that it is non‐magnetic down to 30 mK with the Kondo temperature T K = 2.4 K. The HF state is evidenced by the large value of the electronic specific heat coefficient γ = 3.3 J mol −1 K −2 . Our previous studies of the thermopower have revealed the presence of a large positive peak at 28 K that has been ascribed to the crystal electric field (CEF) effect leading to an average split of the ground state of the order of Δ = 64 K .…”
Section: Introductionmentioning
confidence: 94%
“…CeCu 4 Ga has been already widely studied and it was verified that it is non‐magnetic down to 30 mK with the Kondo temperature T K = 2.4 K. The HF state is evidenced by the large value of the electronic specific heat coefficient γ = 3.3 J mol −1 K −2 . Our previous studies of the thermopower have revealed the presence of a large positive peak at 28 K that has been ascribed to the crystal electric field (CEF) effect leading to an average split of the ground state of the order of Δ = 64 K .…”
Section: Introductionmentioning
confidence: 94%